2007
DOI: 10.21608/erjm.2007.69895
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Solid Flow Through Ejector

Abstract: Single-phase (air-air) and two-phase (air-solid) flows throngh ejector are numerically and experimentally studied in this paper. The numerical model is performed using continuity equation for the gas phase and the solid phase separately, and the momentum equation for a homogenous mixture of gas-solid flow. The model takes into account the gas and solid friction with the wall and the drag force exerted on a particle by the gas. Three different geometries of the ejector are studied numerically and experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As seen from Table 1 and according to [1] the mixing tube length has significant effect on the mixing of the primary and secondary flows. Ejector performance of [6,7] was carried out for different ejector geometries with fixed mixing tube length 10 times the mixing tube diameter. In the experimental investigation given in [8], the results showed that mixing tube length seems to have no obvious effect and changes of L/D ratio from 2 to10 results give in a slight decrease in the efficiency of ejector.…”
Section: -Introductionmentioning
confidence: 99%
“…As seen from Table 1 and according to [1] the mixing tube length has significant effect on the mixing of the primary and secondary flows. Ejector performance of [6,7] was carried out for different ejector geometries with fixed mixing tube length 10 times the mixing tube diameter. In the experimental investigation given in [8], the results showed that mixing tube length seems to have no obvious effect and changes of L/D ratio from 2 to10 results give in a slight decrease in the efficiency of ejector.…”
Section: -Introductionmentioning
confidence: 99%